Mission failure : America and the world in the post-Cold War era - Mandelbaum, Michael (Oxford University Press, 2016)
"In Mission Failure, Mandelbaum argues that, in the past 25 years, U.S. foreign policy has undergone a significant shift. Historically, U.S. foreign policy was oriented primarily toward threat reduction, but the U.S. military has turned in recent years to missions that are largely humanitarian and socio-political. Mandelbaum argues that ideologically-driven foreign policy--that which seeks to reconstruct societies along Western lines--generally leads to mission failure"--